IS IT FAIR TO ASSESS THE PERFORMANCE OF ISLAMIC BANKS BASED ON THE CONVENTIONAL BANK PLATFORM? - Elyanti Rosmanidar; Muhamad Ahsan; Abu Azam Al-Hadi; Nguyen Thi Minh Phuong (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Several studies found the weakness of using conventional performance measurement tools such as CAMELS and RGEC in Islamic banking and the lack of performance measurement tools following the characteristics of Islamic banks. This is the solid reason to have a performance measurement system that integrates the objectives of sharia and the business objectives of sharia banking. This study explores the application of maqâsid al-sharî‘ah values in Islamic banking and initiated a Sharia Integrated Performance Measurement (SIPM) structure. This is a library research. The primary data were collected through in-depth interviews with practitioners, experts, and academics of Islamic banking, while secondary data was taken from the literature and previous research that discussed the measurement of Islamic banking performance. The data were analyzed through several stages: data reduction, data display, and concluding with the help of the Atlas.ti application version 8. This study wants to contribute to the idea of building a Sharia Integrated Performance Measurement (SIPM) platform through three components: Islamic commercial performance, Islamic social performance, and Islamic macroeconomics performance in Islamic banking.